Cities and Climate Change : Responding to an Urgent Agenda - Hoornweg, Daniel (World Bank, 2012)
The 5th urban research symposium on cities and climate change responding to an urgent agenda, held in Marseille in June 2009, sought to highlight how climate change and urbanization are converging to create one of the greatest challenges of our time. Cities consume much of the world's energy, and thus produce much of the world's greenhouse gas emissions. Yet cities, to varying extents, are also vulnerable to climate change impacts, with poor populations facing the greatest risk. Thus, adaptation and increased resilience constitute priorities for every city, and cities have a key role to play in mitigating climate change. Climate change mitigation and adaptation in cities has emerged as a new theme on the global agenda, creating a strong desire among governments, the private sector, and the academic community worldwide to learn from experiences and good practice examples. The 5th urban research symposium made an important contribution to the growing body of knowledge and practice in the area of cities and climate change. During the three-day symposium, approximately 200 papers were presented to more than 700 participants representing more than 70 countries. As co-organizers, the authors found it very rewarding to have such an audience and to see the wide range of topics discussed, from indicators and measurement to institutions and governance. This publication is comprised of an edited selection of the many papers submitted to the symposium and gives a flavor of the questions asked and possible answers. (The entire collection of symposium papers is available as an online resource for interested readers.) The authors look forward to the benefits that the knowledge gained and the partnerships forged during the symposium will have for global efforts on cities and climate change.